Childhood trauma and social resources moderate relationships between perceived discrimination and late‐life cognition in older African Americans. (31st December 2021) - Pugh, Erika; Divers, Ross; Calamia, Matthew
Abstract: Background: Perceived discrimination (PD) is a common stressor for African Americans (AA) that has been linked to poorer cognition in old age, although factors that increase or decrease this association remain understudied. For example, a history of childhood trauma, for which African Americans are at greater risk, may affect later cognition by making individuals more stress reactive. In contrast, there may be other factors (e.g. socioeconomic status, access to cognitively stimulating resources) that buffer the negative association between PD and cognition. The purpose of this study was to examine these possible moderators of the association of PD with cognition in a sample of older AAs (n = 583), Method: Data was obtained from the Minority Aging Research Study (MARS), a longitudinal, epidemiologic cohort study of cognitive decline and risk of AD in older (65+) AAs. Moderation analyses were conducted to identify the potential effects of childhood trauma and protective factors on the relationship between PD and cognition, Result: Childhood trauma, specifically greater parental violence, increased the negative association between PD and perceptual speed. Additionally, both early childhood socioeconomic status and access to resources that support cognitive activities throughout one's life decreased the negative association between PD and both global cognition and working memory, Conclusion: In sum, experiencing childhood trauma significantly impacts the effects of PD on cognition in older AAs, representing a key target for interventions. Protective factors, particularly access to cognitively stimulating resources throughout one's life, may represent an actionable target for promoting cognitive wellbeing in older AAs.